Suppression of rpoH (htpR) mutations of Escherichia coli: heat shock response in suhA revertants. - Tobe, T (1987)
Temperature-resistant pseudorevertants were isolated from rpoH (htpR) mutants of Escherichia coli K-12 that cannot grow at a high temperature owing to a deficiency in sigma 32 required for the induction of heat shock proteins. Among them was a class of revertants carrying a suppressor mutation, designated suhA, that suppressed all the nonsense and missense rpoH mutations tested. suhA is located at 77 min, about 1 min away from rpoH, on the genetic map. In contrast to the rpoH mutants, the suhA revertants that contained both rpoH (nonsense) and suhA mutations were fully or partially proficient in the induction of heat shock proteins upon exposure to a high temperature. Under these conditions, transcription from two heat shock promoters as determined by operon fusion was transiently activated. In one of the rpoH(Am) suhA revertants studied in detail, an increase in temperature caused the synthesis of significant amounts of sigma 32, accompanied by increased stability and accumulation of rpoH mRNAs. On the other hand, the same mutation (suhA6) only weakly suppressed the rpoH deletion mutant; however, two of the major heat shock genes, dnaK and groE, were apparently induced in the absence of sigma 32. Thus, suhA6 seems to bring about the induction of heat shock genes by at least two mechanisms, one increasing the level of sigma 32 synthesis, and the other activating some transcription factor other than sigma 32.